Delayed sleep–wake phase disorder and its related sleep behaviors in the young generation - Futenma, Kunihiro; Takaesu, Yoshikazu; Komada, Yoko; Shimura, Akiyoshi; Okajima, Isa; Matsui, Kentaro; Tanioka, Kosuke; Inoue, Yuichi (Frontiers in Psychiatry, 2023)
Delayed sleep–wake phase disorder (DSWPD) is a sleep disorder in which the habitual sleep–wake timing is delayed, resulting in difficulty in falling asleep and waking up at the desired time. Patients with DSWPD frequently experience fatigue, impaired concentration, sleep deprivation during weekdays, and problems of absenteeism, which may be further complicated by depressive symptoms. DSWPD is typically prevalent during adolescence and young adulthood. Although there are no studies comparing internationally, the prevalence of DSWPD is estimated to be approximately 3% with little racial differences between Caucasians and Asians. The presence of this disorder is associated with various physiological, genetic and psychological as well as behavioral factors. Furthermore, social factors are also involved in the mechanism of DSWPD. Recently, delayed sleep phase and prolonged sleep duration in the young generation have been reported during the period of COVID-19 pandemic-related behavioral restrictions. This phenomenon raises a concern about the risk of a mismatch between their sleep–wake phase and social life that may lead to the development of DSWPD after the removal of these restrictions. Although the typical feature of DSWPD is a delay in circadian rhythms, individuals with DSWPD without having misalignment of objectively measured circadian rhythm markers account for approximately 40% of the cases, wherein the psychological and behavioral characteristics of young people, such as truancy and academic or social troubles, are largely involved in the mechanism of this disorder. Recent studies have shown that DSWPD is frequently comorbid with psychiatric disorders, particularly mood and neurodevelopmental disorders, both of which have a bidirectional association with the pathophysiology of DSWPD. Additionally, patients with DSWPD have a strong tendency toward neuroticism and anxiety, which may result in the aggravation of insomnia symptoms. Therefore, future studies should address the effectiveness of cognitive-behavioral approaches in addition to chronobiological approaches in the treatment of DSWPD.